2020
DOI: 10.26611/10141513
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental oxygen on development of retinopathy of prematurity

Abstract: Background: Retinopathy of prematurity (ROP) which is also known as retrolental fibroplasia is a vasoproliferative disorder that affects premature infants. Despite of major advancement in management, it continues to be a leading cause of childhood blindness throughout the world. As there had been very few studies conducted here and very few information regarding this disease are available we conducted this study. Aim of the study: The aim of this study was to evaluate the effect of supplemental Oxygen on devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 16 publications
(18 reference statements)
0
4
1
Order By: Relevance
“…These findings are consistent with those reported in several other studies. 4,5,[8][9][10] However, the observed range of FiO2 in this study contradicts the findings by Das, et al, 4 who reported an association of ROP with FiO2 ranging from 0.41 to 0.60. This discrepancy could stem from differences in the timing of outcome measurements.…”
Section: Discussioncontrasting
confidence: 76%
See 3 more Smart Citations
“…These findings are consistent with those reported in several other studies. 4,5,[8][9][10] However, the observed range of FiO2 in this study contradicts the findings by Das, et al, 4 who reported an association of ROP with FiO2 ranging from 0.41 to 0.60. This discrepancy could stem from differences in the timing of outcome measurements.…”
Section: Discussioncontrasting
confidence: 76%
“…2 Interestingly, this study not only highlighted the role of oxygen concentration, but also demonstrated that the duration of oxygen therapy in the ROP group was significantly longer compared to the non-ROP group, a finding consistent with previous studies. 4,5,[11][12][13] Moreover, the relationship between oxygen therapy duration and ROP severity was substantiated by a mean difference regression analysis. The results revealed a statistically significant correlation between the duration of oxygen therapy and the severity of ROP.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…8,12 Some previous studies reported that oxygen supplementation was associated with ROP due to its effect on retinal vessel development: supplemental oxygen can interfere with oxygen tension and a high concentration of oxygen can lead to oxidative stress, which increases retinal ischemia, resulting in ROP. 1,9,11,12,18 Factors related to oxygen supplementation, by CPAP and/or mechanical ventilation remained statistically significant on multivariate analysis. Reyes et al and Akkawi et al also found that invasive ventilation, oxygen therapy increase the risk of developing ROP.…”
Section: Discussionmentioning
confidence: 91%